Kekuasaan dan Kewenangan Kyai Desa (Analisis Pengaruh Kyai Desa dalam Pengelolaan Pendidikan Nonformal di Madura) - Rohmah, Mawadatur (Civiliza Publishing, Indonesia., 2023)
The purpose of this study is to determine the power and authority of village clerics in building community participation in the village, both in terms of academics, socio-economics, religion, and so on. This study discusses the power and authority of village clerics who have an important role in inviting, influencing, guiding, and creating a good civilization in a village. This study uses a qualitative approach with a phenomenological type. A qualitative approach is used to reveal the meaning behind an undertstanding of meaning action, where this study describes and depicts a phenomenon as it is without any data manipulation in it. The data collection technique for this study uses a deep interview technique, namely by asking questions to the resource person about a topic raised, deep interviews are not only conducted face-to-face, but can also be done via telephone or video call. Deep interviews are conducted when we want to know what each individual respondent thinks to get in-depth information. Based on this study, it can be concluded that the power and authority of village clerics can be determined from the power and type of traditional authority and charismatic authority that is built and educated in the village cleric. In the traditional authority type, it appears because of the paternalistic culture among the Madurese community. The paternalistic culture in Madura is established between the Kyai and the santri as is the relationship between a father and a child, where a village Kyai has the status of a protector, teacher, and father. Likewise in the charismatic type, the authority and power possessed by the village Kyai in Madura also appears because of the charisma inherent in the village Kyai. This charisma is caused by the behavior, nature, and competence possessed by the village Kyai. Among the behavior, nature, and competence possessed by the village Kyai.